Individuality in music performance - Bruno Gingras (Frontiers Research Topics, 2014)
Humans are remarkably adept at identifying individuals on the basis of their facial features, or other traits such as gait or vocal timbre. Besides voice, another auditory medium capable of carrying identity information is music. Indeed, certain famous musicians, such as John Coltrane or Sonny Rollins, need only to play a few notes to be unequivocally recognized. Along with emotion and structural cues, artistic individuality seems to be a key element communicated in music performance. Yet, the means by which individuality is expressed in performance, as well as the cognitive processes employed by listeners to perceive identity cues, remain poorly elucidated. Other pertinent issues, including the connection between a performer's technical competence and ability to convey a specific musical identity, as well as potential links between individuality and career-defining outcomes such as critical recognition and aesthetic appraisal, warrant further exploration. Quantitative approaches to the study of music performance have benefited greatly from MIDI technology and the application of computational methods, leading to the flourishing of empirical music performance research over the last few decades. More recently, neuroimaging techniques have provided valuable insights into the neural mechanisms involved in the cognitive processes of performing music. Nevertheless, this field continues to benefit greatly from qualitative approaches, given that the communication of affect and identity cues in music performance leads to a rich subjectivity of impressions that must be accounted for in order to lead to a greater understanding of this multifaceted phenomenon. The aim of this Research Topic is to provide a forum for interdisciplinary research broadly related to the expression and perception of individuality in music performance. Research methodology includes behavioral, psychophysiological, and neuroimaging techniques. Both quantitative and qualitative approaches are presented The scope of this Research Topic includes laboratory studies as well as studies in real-life performance settings and longitudinal studies on performers.